Vaginal progesterone in risk reduction of preterm birth in women with short cervix in the midtrimester of pregnancy - Khandelwal M (Dove Medical Press, 2012)
Meena KhandelwalDepartment of Obstetrics and Gynecology, Cooper University Hospital, Camden, NJ, USAAbstract: Preterm birth is a major health problem for the neonate, family, country, and society in general. Despite many risk factors being identified for women destined to deliver preterm, short cervical length detected on transvaginal ultrasound is the most plausible, practical and sensitive risk factor for prediction of spontaneous preterm birth. The definition of short cervix has varied in various studies, but most commonly accepted is #2.5 cm in the midtrimester of pregnancy, though risk of spontaneous preterm birth (sPTB) increases as the cervical length decreases. Vaginal progesterone, a naturally occurring steroid hormone, is the most bioavailable form of progesterone for uterine and cervical effects with the fewest side effects. Multiple prospective studies have consistently shown its benefits in decreasing sPTB rate in women with asymptomatic midtrimester short cervix. The safety for mother and fetus, and tolerability of vaginal progesterone, particularly the gel form, is also well established. Vaginal progesterone is a minimally invasive intervention that is not painful and is very safe, with reasonable cost where the benefits (even if argued to be small) clearly outweigh the risks. Thus there should be little hesitation for implementation of universal transvaginal cervical length screening and preventive vaginal progesterone treatment for women with short cervix.Keywords: preterm birth, progesterone, short cervix